EFFECT OF CHEWING POLYOLS GUMS ON THE ACCUMULATION OF DENTAL PLAQUE AROUND ORTHODONTIC BRACKETS: EFEK MENGUNYAH PERMEN KARET POLYOL TERHADAP AKUMULASI PLAK DI SEKITAR PERLEKATAN BRAKET - Tri Erri Astoeti; Hendra Kurniawan; Widijanto Sudhana; Harijanto Wijaya (TALENTA, 2011)
This study aimed to investigate the effect of xylitol compared to sorbitol as polyols chewing gum on the plaque accumulation during treatment with fixed orthodontic appliances. This clinical trial comprised 20 healthy orthodontic patients aged 18 –to-30-years old. The subjects were randomly assigned into 2 groups: xylitol group (n=10) and sorbitol group (n-10). The subjects were instructed to chew 2 pieces of tested chewing gum three times everyday for a 14-days period of experiment. The xylitol gum contained of 1300 mg xylitol per serving (2 pieces of gum) while the sorbitol gum was sweetened with sorbitol. At baseline and after 14 days the plaque were collected from bucco-cervical surfaces around brackets of premolar and front teeth and then dried weigh. The result of this study showed that the means of plaque weight in the xylitol group at baseline and after 14 days were 2.75 mg ± 2.59 mg and 0.92 mg ± 1.23 mg respectively, while the means of plaque weight in the sorbitol group at baseline and after 14 days were: 2.13 mg ± 0.94 mg and 2.37 mg ± 0.89 mg respectively. After one way ANOVA and post hoc test, there was no difference between plaque weight in both groups at baseline (p=0.2) while the plaque weight in the xylitol group was significantly lower than the sorbitol group after 14 days (p < 0.01). In conclusion, 14-days use of xylitol- containing chewing gums, corresponding to a daily amount of 4 grams of xylitol, could eliminate the plaque accumulation in fixed orthodontic patients.